An injectable scaffold based on temperature‐responsive hydrogel and factor‐loaded nanoparticles for application in vascularization in tissue engineering. Issue 10 (24th May 2019) - He, Dan; Zhao, An‐Sha; Su, Hong; Zhang, Yan; Wang, Ya‐Nan; Luo, Dan; Gao, Yuan; Li, Jing‐An; Yang, Ping
Abstract: Controlled release of functional factors contributes to target migration of therapeutic cells and plays a crucial role in the in situ vascularization of tissue repair and regeneration. A biomedical application requires the selective release of multiple factors which will guide the synergy of the cells. Here, we developed an injectable system based on a temperature‐responsive hydrogel and stromal cell‐derived factor‐1 (SDF‐1)/vascular endothelial growth factor (VEGF) loaded into two types of nanoparticles to induce migration and rapid proliferation of mesenchymal stem cells (MSCs) and endothelial cells (ECs) via selective SDF‐1/VEGF release. Series of in vitro and in vivo experiments demonstrate that our composited system can accurately guide MSCs and ECs for vascularization. In addition, the properties of the nanoparticles and hydrogel, including micro/nanoscales, characteristic of charge, and biocompatibility, played crucial roles for the selective release and cells behavior (target migration and rapid proliferation).